Rancang Bangun Sistem Penjualan Toko Optik Berbasis Web Menggunakan Metode Waterfall - Willis Puspita Sari; Agus Heri Yunial (Teknik Informatika Universitas Pamulang, 2021)
The decline in community activities outside the home and restrictions on operating hours in the business world have a negative impact on the income and performance of the business world. This is the impact of restrictions on activities outside the home carried out by the government in order to reduce the spread of the covid 19 virus. For this reason, an innovation is needed that changes management governance and trade transactions that switch to online, so that business activities can run and remain active in the midst of current pandemic. One of the businesses affected by the impact is the Sinar Pratama Optical Shop in Gunung Sindur, which has limited operating hours and the number of visitors has decreased due to limited activities outside the home. Another problem at this time at the store is the time for making eyeglass sales reports which are quite long, and still using 3 copies of receipts for 1 sales transaction. To overcome this problem, an eyewear sales management information system was created, which can handle sales data and can make reports anywhere and anytime. Waterfall was chosen in the method used because it is considered more suitable if the need for each process is known. With the waterfall method, the creation of a web-based sales application at the Sinar Pratama Optical Shop can be completed in a predetermined time and the Sinar Pratama Optical Shop can sell goods and promotions on its own website and can compete during the current pandemic. In addition, making sales reports can be done more quickly because of the computational process and can be done anywhere.